Protecting Victims Privacy in Cinematographic Works: A Juridical Analysis of Freedom of Expression in the Film ‘Vina Sebelum 7 Hari’: Perlindungan Hak Privasi Korban dalam Karya Sinematografi: Analisis Yuridis terhadap Kebebasan Berekspresi dalam Film ‘Vina Sebelum 7 Hari’ - Sunan Autad Sarjana; Atifah Rohmah Fani; Hifdhotul Munawaroh; Iman Nur Hidayat; Rashda Diana (Journal of Indonesian Comparative of Syari'ah Law, 2026)
Films serve as educational media and convey moral messages, but they differ when they portray the true story of a victim of sexual violence by exposing their true identity without protection. The film